Stagnant forearc mantle wedge inferred from mapping of shear-wave anisotropy using S-net seafloor seismometers - Naoki Uchida (Nature Portfolio, 2020)
Knowledge of shear-wave anisotropy is important to understanding the structure and dynamics of the subduction zone mantle wedge. Here, the authors find unambiguous evidence that forearc anisotropy resides in the upper-plate crust, while weak anisotropy in the most seaward part of the mantle wedge indicates decoupling from the slab